Artificial Intelligence and the Future of Work in Southeast Asia: A Desktop Study of Opportunities, Challenges, and Workforce Readiness - Alan, Alan Robert White; Darodjat, Tubagus Achmad; Maryano, Maryano (PENANOMICS: International Journal of Economics, 2025)
Artificial Intelligence (AI) is redefining the global labor landscape, presenting both opportunities for economic growth and risks of workforce displacement. This desktop study investigates the impact of AI on employment trends in Southeast Asia, with a focus on how regional economies such as Singapore, Indonesia, and Thailand are adapting. Drawing from recent literature, policy analysis, and international reports, the study identifies workforce readiness, inclusive skilling initiatives, and collaborative governance as critical factors for harnessing AI’s benefits. Findings suggest that despite progress in digital infrastructure and training investments, the region faces significant challenges related to inequality, preparedness, and digital skill gaps. The paper concludes by recommending comprehensive policies for inclusive AI adoption, sustained investment in education, and adaptive labor systems.